Integrated multifunctional flexible electronics based on tough supramolecular hydrogels with patterned silver nanowires. Issue 23 (9th June 2020) - Zhu, Fengbo; Zheng, Si Yu; Lin, Ji; Wu, Zi Liang; Yin, Jun; Qian, Jin; Qu, Shaoxing; Zheng, Qiang
Abstract : A hybrid conductive hydrogel system was facilely integrated with complex circuits. The obtained hydrogel electronics show excellent mechanical and electrical performances, enable monitoring tensile strain, pressure, and temperature. Abstract : Conductive hydrogel based soft electronics with superior mechanical/electrical properties and biocompatibility have great potential for sensing and stimulation at device–human interfaces, in which one piece of the functional gel is usually used as a multi-sensor to chemicals, mechanical deformations, etc. Also, it is important to develop a facile strategy for patterning intricate circuits and conductive components in a hydrogel system to afford integrated functions. Demonstrated here is a hybrid conductive hydrogel system that can be facilely patterned and integrated with complex circuits, which enables monitoring of multiple signals, including tensile strain, out-of-plane pressure, and temperature. The conductive hydrogel was fabricated by a stencil-aided printing of percolated silver nanowires (AgNWs) on a tough supramolecular hydrogel with robust interfacial bonding. The obtained hydrogel-based electronics exhibited remarkable electrical and mechanical properties, with a sheet resistance of 0.76 Ω sq −1, breaking strain of over 600%, breaking stress up to 3.3 MPa, and self-healing ability, superior to most existing conductive hydrogels. The strain sensors exhibited a gauge factor up to 58.2, enabling monitoring various subtle human motions. Multiple sensing units can be facilely fabricated in this approach using a well-designed silhouette mask. The powerful functions of the integrated electronics were manifested by the detection of complex stress or temperature fields.